Fabrication of UiO-66/MIL-101(Fe) binary MOF/carboxylated-GO composite for adsorptive removal of methylene blue dye from aqueous solutions. Issue 32 (19th May 2020) - Eltaweil, Abdelazeem S.; Abd El-Monaem, Eman M.; El-Subruiti, Gehan M.; Abd El-Latif, Mona M.; Omer, Ahmed M.
Abstract : This study provides a novel composite as an efficient adsorbent of cationic methylene blue dye. Abstract : This study provides a novel composite as an efficient adsorbent of cationic methylene blue dye. UiO-66/MIL-101(Fe) binary metal organic framework (MOF) was fabricated using a solvothermal technique. Additionally, the developed binary MOF was modified with carboxylated graphene oxide (GOCOOH) using a post-synthetic technique. The as-fabricated UiO-66/MIL-101(Fe)-GOCOOH composite was analyzed by FTIR, XRD, SEM, BET, TGA, XPS and zeta potential analysis. The adsorption performance of UiO-66/MIL-101(Fe)-GOCOOH composite was examined for its aptitude to adsorb cationic MB dye using a batch technique. The obtained data revealed that, the developed UiO-66/MIL-101(Fe)-GOCOOH composite exhibited higher adsorption capacity compared to UiO-66/MIL-101(Fe) binary MOF. Adsorption isotherms and kinetic studies revealed that MB dye adsorption onto UiO-66/MIL-101(Fe)-GOCOOH composite fitted a Langmuir isotherm model ( q m = 448.71 mg g −1 ) and both pseudo 1 st order and pseudo 2 nd order kinetic models. An intra-particle diffusion model showed that the adsorption process occurs through three steps. Besides, thermodynamic data reflected that the adsorption of MB onto UiO-66/MIL-101(Fe)-GOCOOH composite is an endothermic and spontaneous process and the adsorption involves both physisorption and chemisorption interactions. The as-fabricated UiO-66/MIL-101(Fe)-GOCOOH composite exhibited good reusability and can be considered as a promising reusable adsorbent for the treatment of dye-containing industrial effluents with high efficiency.